Antipyretic Activity of Some Plant Species of The Genus Hibiscus And Genus Citrus: Review Articles - Asman Sadino; Suwendar Suwendar; Lani Husni Awaliah (Buletin Farmatera, 2023)
Abstract: Traditional medicine is one of the great benefits for the community in building health, for example, such as using medicinal plants as an alternative to traditional treatment, one of which is reducing fever. This review aims to find and evaluate the scientific literature on plants with antipyretic effects of the genera Hibiscus and Citrus. The research approach used in this article review is a literature review based on journals published in the last ten years (2012-2022) collected from national and international journals and conducted online using Google scholar, Pubmed, and NCBI search engines. The results of the review related to plants that have antpyretic activity from the Hibiscus Genus and Citrus Genus as many as 8 plant species,  namely Hibiscus rosa sinensis, Hibiscus tiliaceus L, Hibiscus sabdariffa, Hibiscus schizopetalus (MAST.) HOOK, Citrus aurantifolia (Christm) Swing, Citrus hystrix, Citrus  x aurantium L and Citrus assamensis.